Applying Sewage Sludge to Eucalyptus grandis Plantations: Effects on Biomass Production and Nutrient Cycling through Litterfall - Paulo Henrique Müller da Silva; Fabio Poggiani; Jean Paul Laclau (Applied and Environmental Soil Science)
In most Brazilian cities sewage sludge is dumped into sanitary landfills, even though its use in forest plantations as a fertilizer and soil conditioner might be an interesting option. Sewage sludge applications might reduce the amounts of mineral fertilizers needed to sustain the productivity on infertile tropical soils. However, sewage sludge must be applied with care to crops to avoid soil and water pollution. The aim of our study was to assess the effects of dry and wet sewage sludges on the growth and nutrient cycling of Eucalyptus grandis plantations established on the most common soil type for Brazilian eucalypt plantations. Biomass production and nutrient cycling were studied over a 36-month period in a complete randomized block design. Four experimental treatments were compared: wet sewage sludge, dry sludge, mineral fertilizer, and no fertilizer applications. The two types of sludges as well as mineral fertilizer increased significantly the biomass of Eucalyptus trees. Wood biomass productions 36 months after planting were similar in the sewage sludge and mineral fertilization treatments (about 80 tons ha−1) and 86% higher than in the control treatment. Sewage sludge application also affected positively leaf litter production and significantly increased nutrient transfer among the components of the ecosystem.